Medusa - Cussler, Clive; Kemprecos, Paul.; Brick, Scott ([New York, N.Y.] : Penguin Audio, 2009)
Clive Cussler and Paul Kemprecos present the eighth NUMA File novel. Kurt Austin and his National Underwater and Marine Agency Special Projects team return, squaring off with the elusive and dangerous Pyramid Triad organization of China in a race to acquire the antidote for a bizarre pandemic viral disease. The Triad wants the virus and the cure in order to hold the world hostage; only NUMA stands in the way of its apocalyptic machination.
Title from web page.
Unabridged.
Compact discs.
Duration: 14:00:00.
Read by Scott Brick.
Keywords: Austin, Kurt (Fictitious character) -- Fiction; Marine scientists -- Fiction; Medicine -- Research -- Fiction; Viruses -- Fiction; Suspense fiction; Adventure fiction; Audiobooks